Recent development and efficacy of wire mesh embedded natural fiber composite - A review - Elayaraja R; Rajamurugan G (Results in Engineering)
This review examined the current developments in wire mesh reinforced natural fiber composites (WMRCs), emphasizing their material properties, applications, and production techniques. WMRCs provide a sustainable and economical alternative to conventional synthetic composites. Natural fibers (NF), including flax, jute, and hemp, offer superior mechanical characteristics and diminish environmental effects. The incorporation of wire mesh improves the structural integrity of the composite. WMRCs provide exceptional durability and wear resistance, rendering them appropriate for use in the automotive, aerospace, and construction sectors. They provide enhanced mechanical qualities relative to single-fiber reinforced composites. The attributes of the wire mesh, including type, orientation, and material, substantially affect the performance of the composite. This research examines optimum drilling settings for WMRCs utilizing techniques such as Abrasive Water Jet Machining (AWJM). The primary fabrication techniques for WMRCs consist of hand layup and vacuum bag molding, with possibilities for compression molding and pultrusion. In conclusion, WMRCs offer a potential pathway for the advancement of composite materials. Subsequent study ought to concentrate on enhancing wire mesh reinforcement for particular applications, tackling water absorption challenges, and investigating novel wire mesh materials and manufacturing techniques.